Analysis of Judges’ Decision Regarding Cancellation of Waqf Land by Wakif (Study of Analysis of Decisions in Malang Religious Court Number 6551/Pdt.G/2018/PA.Kab.Mlg) - Khairunnisa Khairunnisa; Khalid Khalid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The research aims to understand or obtain information about the review of Islamic law and positive law on the judge’s decision regarding the cancellation of waqf land by the wakif (Analytic Study of Decisions of the Malang Religious Court Number 6551/Pdt.G/2018/PA.Kab.Mlg). In this study, a descriptive qualitative approach was used which described and analyzed the review of Islamic law and positive law on the Cancellation of Waqf in the Malang Religious Court Decision Number 6551/Pdt.G/2018/PA.Kab.Mlg. The results of the study show that the juridical review of the waqf laws and regulations regarding the cancellation of waqf by the waqif in waqf disputes that have been decided by the Malang Religious Court in Decision Number 6551/Pdt.G/2018/PA.Kab.Mlg. that the waqf can be canceled because the waqf made at that time did not fulfill some of the waqf elements and requirements listed in Law Number 41 of 2004 concerning Waqf.